High CD14 antigen expression in urothelial bladder carcinoma establishes that the inflammatory microenvironment promotes tumour cell proliferation - Ahmad, Aiful; Mohd Yusoff, Suryati; Mohd Ali, Razana; Osman, Malina; Lai, Shau Kong; Hussin, Huzlinda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: CD-14 is an antigen found on the bladder cancer cells that mediated cancer development by providing a supportive inflammatory microenvironment. The study investigates the association of CD14 antigen expression in bladder cancer cells with demographic factors, clinicopathological parameters and recurrent cases by immuno- histochemical (IHC) method. Methods: A retrospective study using 59 formalin-fixed paraffin-embedded tissue of urothelial bladder carcinoma cases were subjected to CD14 IHC staining. Results: Most patients were  65 years old (57.6%), Malay in ethnicity (55.9%) and male predominant (94.9%). CD14 was positively expressed in more than 50% of tumour cells in all grades and stages with the largest percentage seen in the highest grade (Grade III) and stage (Stage IV) of urothelial bladder carcinoma. There was a significant association between CD14 expression and tumour grade of urothelial bladder carcinoma (p = 0.043). However, there was no significant association between CD14 expression with demographic factors, tumour stage or recurrent cases. Conclusion: High CD14 antigen expression by cancer cells establishes that the inflammatory microenvironment promotes tumour cell growth and may suggest CD14 antigen as a poor prognostic marker in urothelial bladder carcinoma.